Determinants of Self-Medication With Antibiotics in European and Anglo-Saxon Countries: A Systematic Review of the Literature - Lescure, Dominique; Paget, John; Schellevis, Francois; van Dijk, Liset (Frontiers in Public Health, 2018)
Background: Self-medication with antibiotics, which comes in different forms (e.g. leftover or over-the-counter use), contributes to antimicrobial resistance as it often happens in a non-prudent manner. In order to tackle this persistent public health problem, its drivers need to be known. The aim of this study was therefore to identify determinants of self-medication with antibiotics via a systematic literature review. Methods: A comprehensive search on determinants of self-medication with antibiotics in the ambulatory care was conducted in PubMed, Scopus and Embase for studies published between January 2000 and March 2017. There was no limit on the language nor on the type of study. The search was restricted to European and Anglo-Saxon countries. Pairs of reviewers independently screened the abstracts and full texts and performed a quality assessment. Results: From the initial 664 abstracts, 54 publications that included 44 countries were retrieved of which most identified patient related determinants. Important determinants include storing antibiotics at home, poor access to healthcare, and having the intention to self-medicate. Healthcare professionals contribute to the practice of self-medication when catering for demanding and socially vulnerable patients. Healthcare system related determinants include dispensing antibiotics in whole packages and the lack of enforcement of medicine regulations. For some determinants (e.g. patients’ age) contradictory results were found. Conclusion: Self-medication with antibiotics is driven by a variety of determinants on the patient, healthcare professional and system levels. Policy makers should recognise the complexity of self-medication in order to develop multifaceted interventions that target healthcare professionals and patients simultaneously.